Strategi Komunikasi Pemasaran Sosial Pendidikan Tertib Berlalu Lintas pada Kalangan Anak Usia Dini - Wijaya, Sri Herwindya Baskara; Alkhajar , Eka Nada Shofa; Anshori, Mahfud; Tiyanto, Dwi; Sulihyantoro, Aryanto Budhy; Candra Wijaya, Deniawan Tommy; Primasari, Ina; Setyawan Prabowo, Henricus Hans (WAHANA, 2021)
The problem of underage driving has now become a serious social problem in Indonesia. As a result, there are many accidents that should not have happened. Therefore, traffic education is very important to be done from an early age. This study aims to examine the offline social marketing communication strategies for traffic education carried out by the Klaten Resort Police Traffic Unit. The results of the study found that there were two main strategies in communicating traffic education, i.e.: direct communication and group communication. These two strategies are implemented both for children as educational targets and for the manager of the BERSINAR Traffic Education Park as facilitators. This research also confirmed the importance of traffic education for children at a very early age.